The Impact of Systemic Inflammatory Response Syndrome (SIRS) and Sepsis Training on Pediatric Nurses - Mathema, Smriti; Kayastha, Pawana; Sharma, Pushpa Raj (Journal of Nepalgunj Medical College, 2021)
Introduction: Research demonstrates the importance of key interventions in reducing mortality rates of pediatric patients with sepsis. Of health care practitioners, nurses typically spend the most time with patients, and they must be knowledgeable in recognizing the SIRS and sepsis while also being aware of the importance of prompt intervention.Aims: The purpose of this study is to assess the knowledge of pediatric nurses of SIRS and reassess their knowledge after a sepsis training program.Methods: This time-series design study from February 2017 to February 2019 included 24 nursing staff involved in taking care of pediatric patients. The nurses were divided into two groups and they underwent a one-day training on sepsis. They were the evaluated periodically on their knowledge on pediatric sepsis at four different time points. The retention of knowledge was calculated based on the change in scores, as per mean numeric scores, immediately after the training compared to 12 and 24 months after the training. Results: In the thematic area ‘Early recognition of signs/symptoms of SIRS’ and ‘Assessment of application of knowledge’, there was a significant change (